Cinema and Literature in Brazil and in Spain during the 1950s: Contributions of Neorealism and Speculative Fiction - Araújo, Naiara Sales; Lorenzo Quiles, Oswaldo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
he present study aims at discussing the cinematographic production of the 1950s in Brazil and in Spain, taking into account social and cultural changes in the world after 1945. It seeks to show how the cinema of these countries was influenced by techno-scientific advances and literary tendencies arising from the process of technological development. Based on the notes of Brazilian and Spanish cinema researchers, it is possible to say that there are significant similarities in the cinematographic scenarios of these coun - tries, as they were influenced by the same ideological and production tendencies. The results point to an important influence of Italian neorealist aesthetics in both countries, as well as to a significant contribution from literary speculative genres, in order to obtain an aesthetically more realistic and attractive language